Design of dual and Wideband Rectangular Patch Antenna for C and X Band Applications - Lakrit, S. (Advanced Electromagnetics, 2018)
In this paper, we resolve two issues of microstrip antennas, which are miniaturization and efficiency behavior. For that, a rectangular patch antenna with 16×18×1.6 mm3 dimensions with dual-band characteristics, was designed, fabricated and characterized. In order to improve the problem of narrow bandwidth in microstrip antennas, we implement in this study the slot technique, allowing us to achieve our purpose. This technique, lead to a good reflection coefficient and VSWR. The characteristics of the fabricated antenna were measured and analyzed by Vector Network Analyzer. The results show two resonance frequencies that define two bandwidths defined by a return loss less than -10 dB and are respectively; 7.47 GHz at a frequency of 400 MHz, and 11.01 GHz at a frequency of 790 MHz. Also, the obtained gain has a good value and it’s very remarkable according to the small size of the structure, with a peak value of 6.1 dB at 12.5 GHz. The small size and good characteristics enlarged the applications domains of our structure, from telecommunications and especially Radar, satellite communications to medical and wireless applications.